1994
DOI: 10.1209/0295-5075/28/5/008
|View full text |Cite
|
Sign up to set email alerts
|

Optical Evidence of Anderson-Mott Localization in FeSi

Abstract: Anderson-Mott localization behaviour of the low-temperature optical conductivity, while at high frequencies the excitation spectrum resembles that of a conventional semiconductor. The missing spectral weight below the gap energy is redistributed around the gap edge, in disagreement with previous claims based on optical measurements.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
59
2

Year Published

1995
1995
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(72 citation statements)
references
References 16 publications
11
59
2
Order By: Relevance
“…Another unusual feature that also suggests the presence of strong correlations in FeSi is that the spectral weight expelled from the gap region is spread over a frequency range more than 1 eV above the gap. The results by DeGiorgi et al 36 are in disagreement with those findings, but as was noted earlier their sample is apparently more metallic and probably not representative for the intrinsic behavior of FeSi. 19 We, therefore, compare our results below to those obtained by Damascelli et al 22 who performed their measurements on the same high-quality single crystals that we used for tunneling spectroscopy.…”
Section: Comparison To Other Spectroscopic Techniquesmentioning
confidence: 62%
“…Another unusual feature that also suggests the presence of strong correlations in FeSi is that the spectral weight expelled from the gap region is spread over a frequency range more than 1 eV above the gap. The results by DeGiorgi et al 36 are in disagreement with those findings, but as was noted earlier their sample is apparently more metallic and probably not representative for the intrinsic behavior of FeSi. 19 We, therefore, compare our results below to those obtained by Damascelli et al 22 who performed their measurements on the same high-quality single crystals that we used for tunneling spectroscopy.…”
Section: Comparison To Other Spectroscopic Techniquesmentioning
confidence: 62%
“…We see, that for CoSi the N m e /m * (ω)-curves for different temperatures merge above 1000 cm −1 indicating that no transfer of spectral weight from high to low frequencies takes place. For FeSi the recovery of spectral weight can be followed upto approximately 2000 cm −1 above which the experimental errorbars become rather large as a result of uncertainties in the KramersKronig analysis, mainly induced by the extrapolations at high frequency [9,10]. It seems plausible to associate the temperature dependence of the section between 1000 and 2000 cm −1 with the optical conductivity due to thermally induced charge carriers.…”
Section: Optical Propertiesmentioning
confidence: 99%
“…In addition, it has been shown that phonon excitations at finite temperature can close the narrow gap, accounting for some of the observed anomalous temperature dependences [24][25][26][27][28][29][30] , in particular the experimental observation of the gap closing [31][32][33] . Possibly strong electronic correlations have also be noted 34,35 , and it has been proposed that that FeSi could be an unusual d−electron Kondo insulator, although this point remains controversial 32,34,[36][37][38][39] . Interest in FeSi also arises from geophysics, as it is a possible reaction product between molten iron and mantle silicates at the core-mantle boundary 14,[40][41][42] .…”
Section: Introductionmentioning
confidence: 99%